2008
DOI: 10.1534/genetics.108.091967
|View full text |Cite
|
Sign up to set email alerts
|

The Pleiotropic Phenotype of Apc Mutations in the Mouse: Allele Specificity and Effects of the Genetic Background

Abstract: Familial adenomatous polyposis (FAP) is a human cancer syndrome characterized by the development of hundreds to thousands of colonic polyps and extracolonic lesions including desmoid fibromas, osteomas, epidermoid cysts, and congenital hypertrophy of the pigmented retinal epithelium. Afflicted individuals are heterozygous for mutations in the APC gene. Detailed investigations of mice heterozygous for mutations in the ortholog Apc have shown that other genetic factors strongly influence the phenotype. Here we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…These lesions were characterized as ductal carcinoma in situ with features similar to human PanINs, IPMN and MCN. We hypothesized that changing the genetic background may affect the neoplastic phenotype as several studies have demonstrated that genetic background may affect the phenotype of transgenic mice 12, 13. We demonstrated that the incidence of pancreatic neoplasia in EL‐Kras FVB mice at 8‐10 months of age was zero percent compared to 92% in age‐matched EL‐Kras F1 mice (12 mice per group) (Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…These lesions were characterized as ductal carcinoma in situ with features similar to human PanINs, IPMN and MCN. We hypothesized that changing the genetic background may affect the neoplastic phenotype as several studies have demonstrated that genetic background may affect the phenotype of transgenic mice 12, 13. We demonstrated that the incidence of pancreatic neoplasia in EL‐Kras FVB mice at 8‐10 months of age was zero percent compared to 92% in age‐matched EL‐Kras F1 mice (12 mice per group) (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…Halberg et al . illustrated the effects of genetic background on an intestinal polyposis model that also developed pancreatic adenocarcinoma (primarily, though not exclusively, acinar in histotype) 13. Mice of 129 and (B6 X 129) F1 backgrounds were mutated for Apc and p 53( Apc Min/+ p 53 −/− ).…”
Section: Discussionmentioning
confidence: 99%
“…Potential roles of genetic or environmental factors have been extensively investigated with these models. For instance, disruption of p53 (9,10) or phosphatase and tensin homolog deleted from chromosome 10 (PTEN) (11,12) or induction of oncogenic Kras (13-15) significantly promoted intestinal tumorigenesis only in the context of APC loss. Protumorigenic effects by active inflammation have been demonstrated by inducing colitis with dextran sodium sulfate (DSS) (16).…”
mentioning
confidence: 99%
“…While the APC gene has been identified to be one of the most important genes that play a role in the development of colorectal cancer, there are multiple proteins that work in parallel with Apc to create these cancers (Sjöblom et al, 2006;Wood et al, 2007). Although the actual mechanisms of selection are not clear, it is known that proteins which are not directly interacting with APC, and have similar functions in a cell-such as tumor suppressor genes PTEN (Marsh et al, 2008), TRP53 (Halberg et al, 2008), and p21 …”
Section: Introductionmentioning
confidence: 99%